Hubungan Bahan Organik dengan Kelimpahan Bakteri Vibrio sp pada Tambak Udang Vaname (Litopenaeus vannamei) Skala Intensif - Yunarty Yunarty; Diana Putri Renitasari; Ardana Kurniaji; Muhammad Hery Riyadi Alauddin; Rahmina Rahmina; Siti Aisyah Saridu (Jurnal Perikanan Unram, 2024)
The cultivation of vannamei shrimp (Litopenaeus vannamei) requires attention to the quality of the rearing water to prevent the occurrence of Vibrio sp. bacterial infections. This study aims to analyze the abundance of Vibrio sp., Total Organic Matter (TOM), and the relationship between organic matter and the abundance of Vibrio sp. in the cultivation media. The research stages include sample preparation, KMnO4 standardization, TOM measurement, equipment sterilization, TCBS media preparation, bacterial inoculation, and the enumeration of Vibrio sp. The data obtained were analyzed for correlation using the SPSS26 application. The results showed that TOM levels in the water samples increased as the cultivation period progressed, with the lowest TOM level being 105 ppm at the early DOC and the highest 223 ppm at the late DOC. The abundance of Vibrio sp. fluctuated, with the lowest being 2,0×102 CFU/mL at DOC 54 and the highest at DOC 89, reaching 3.0×103 CFU/mL. The correlation value between organic matter and Vibrio sp. abundance was 0.486, indicating a moderate relationship and showing a positive linear correlation, meaning the relationship was directly proportional. This study shows that TOM positively correlates with the abundance of Vibrio sp. bacteria in intensive vannamei shrimp farming.